A comparison between Laser Granulometer and Sedigraph in grain size analysis of marine sediments. (November 2018) - Celia Magno, M.; Venti, F.; Bergamin, L.; Gaglianone, G.; Pierfranceschi, G.; Romano, E.
Highlights: Laser Granulometer and X-ray Sedigraph are commonly used for grain size analysis of marine sediments. Both the instruments detected sand in the <63 μm fraction obtained by mechanical sieving. Aggregates of clay minerals were detected as larger particles by both the instruments. Heavy grains were detected as sand by Sedigraph, because it works on the sedimentation principle. These errors were not significant for the interpretation of provenance and distribution of sediments. Abstract: A total of 24 sediment samples with wide dimensional, mineralogical and compositional range were considered, collected from 5 Italian coastal marine sites. The fine fraction (<63 μm) was analyzed using Laser Granulometer (LG) and X-ray Sedigraph (XS) in order to compare data and highlight potential differences. The unexpected variable sandy fraction in nearly all the samples was attributed to clay mineral aggregates. The highest sand percentages detected by XS were attributed to local compositional sediment features. An increase of 15–25% of clay in samples analyzed by XS was attributed to the different working principles of the considered devices. Nevertheless, final results succeeded in characterizing sediment texture and distribution as a function of water depth. In conclusion, it's important to select the analytical instrument according to the characteristics of sediments, to adjust the density of media solution for XS analysis, and to prevent aggregates formation for both XS and LG.